Genome sequencing reveals a deep intronic splicing ACVRL1 mutation hotspot in Hereditary Haemorrhagic Telangiectasia. Issue 12 (22nd September 2018) - Wooderchak-Donahue, Whitney L.; McDonald, Jamie; Farrell, Andrew; Akay, Gulsen; Velinder, Matt; Johnson, Peter; VanSant-Webb, Chad; Margraf, Rebecca; Briggs, Eric; Whitehead, Kevin J; Thomson, Jennifer; Lin, Angela E; et al.
Abstract : Introduction: Hereditary haemorrhagic telangiectasia (HHT) is a genetically heterogeneous disorder caused by mutations in the genes ENG, ACVRL1, and SMAD4. Yet the genetic cause remains unknown for some families even after exhaustive exome analysis. We hypothesised that non-coding regions of the known HHT genes may harbour variants that disrupt splicing in these cases. Methods: DNA from 35 individuals with clinical findings of HHT and 2 healthy controls from 13 families underwent whole genome sequencing. Additionally, 87 unrelated cases suspected to have HHT were evaluated using a custom designed next-generation sequencing panel to capture the coding and non-coding regions of ENG, ACVRL1 and SMAD4 . Individuals from both groups had tested negative previously for a mutation in the coding region of known HHT genes. Samples were sequenced on a HiSeq2500 instrument and data were analysed to identify novel and rare variants. Results: Eight cases had a novel non-coding ACVRL1 variant that disrupted splicing. One family had an ACVRL1 intron 9:chromosome 3 translocation, the first reported case of a translocation causing HHT. The other seven cases had a variant located within a 300 bp CT-rich 'hotspot' region of ACVRL1 intron 9 that disrupted splicing. Conclusions: Despite the difficulty of interpreting deep intronic variants, our study highlights the importance of non-coding regions in the disease mechanism of HHT, particularly the CT-rich hotspot region of ACVRL1 intron 9. The addition of this region to HHT molecular diagnostic testing algorithms will improve clinical sensitivity.